PENGARUH CELEBRITY ENDORSER DAN WORD OF MOUTH TERHADAP MINAT UNTUK BERPINDAH MEREK (BRAND SWITCHING) DENGAN PERCEIVED VALUE SEBAGAI MEDIASI (Studi pada Konsumen Produk Kosmetik Wardah) - Riani, Devi; Soesanto, Harry (Faculty of Economics and Business Diponegoro University, 2015)
Competition in business area which more competitive provides opportunities for consumers to be more flexible for choosing products that are needed or wanted. It does provoke a phenomenon that is increasing and variance of products offered by the company, it’s cause consumers are vulnerable to do brand switching. Because of that, companies need to know how to retain existing customers not to move to the competitor brand. One of the way is to create value (perceived value).The purpose of this study is to analyze the effect of celebrity endorser and word of mouth to perceived value, the effect of perceived value to brand switching, and the effect of celebrity endorser to brand switching. This study is conducted to consumers who have taken certain cosmetics and move to Wardah. The samples in this study were 135 respondents. The method of data collected through questionnaires. The sampling method in this study is a non-probability sampling with purposive sampling technique. This study uses analytical techniques of Structural Equation Model, which is estimated by AMOS 21.0.The Result show that the celebrity endorser has a positive and significant effect on perceived value, word of mouth has a positive and significant effect on perceived value, perceived value has a positive and significant effect on brand switching, but celebrity endorser does not significantly effect on brand switching.